Clinicopathological Variations of Glandular Odontogenic Cyst - Deokar, Varsha (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
Glandular odontogenic cyst (GOC) is an uncommon locally aggressive developmental cyst of the jaw with epithelial as well as glandular characteristics. Gardner et al. termed it as GOC. Clinically they are asymptomatic slow-growing swelling but in a few cases, pain and paraesthesia have been noted. The anterior mandible is the most affected site with a slight male predilection. The highest prevalence is seen in the 5th and 6th decades of life. Radiographically, it may appear as an unilocular or multilocular radiolucency, with well-defined margins. Histologically, GOC reveals a non-keratinized stratified squamous epithelial lining with focal thickenings, micro cysts, and mucous cells, eosinophilic cuboidal or columnar cells (hobnail cells) with subepithelial connective tissue. Due to the overlapping of clinical and radiographic features, it can be misdiagnosed with other lesions like dentigerous cysts, lateral periodontal cysts, and mucoepidermoid carcinoma. For the proper diagnosis and treatment confirmed by histopathology, immunohistochemistry (IHC) markers and molecular studies are needed. The treatment for GOC includes curettage, enucleation, or marsupialization depending on the aggressiveness of the lesion.